LOVE LANGUAGE DI DALAM KELUARGA (Studi Fenomenologi Komunikasi antara Anak dan Orang Tua) - Irena Zhahara (2023)
In this modern era, the relationship between children and parents tends to get less attentive in a family, even though this relationship is crucial because it contributes greatly in shaping the character of a child later on in life. Through love language, both children and parents can learn communicate better so that they are able to better understand what kind of treatment each one likes more in order to create a closer and meaningful relationship. This research aims to find out the meaning of love language for children and parents and whether love language can be a motivation in learning communications to strengthen the relationship between children and parents. In this study, we used a qualitative research method, a descriptive approach, and phenomenological study research. The theory used in this study is the theory of self-disclosure. Data collection was carried out by means of observation, interviews, literature studies, and documentation studies. And for the data analysis, the technique used in this study using the Moustakas data analysis technique. The results of this study found that love language has different meanings depending on the individual, but the ultimate goal remains the same, namely to create a close relationship between children and parents. The meaning of love language itself is to minimize expectations, show concern, make someone feel loved, have reciprocal relationships, form good relationships, encourage, understand other people's feelings, and fulfill needs. Love language can also be a motivation to communicate with children or parents in order to create a closer relationship.